Species complex diversification by host plant use in an herbivorous insect: The source of Puerto Rican cactus mealybug pest and implications for biological control. Issue 19 (20th August 2020) - Poveda‐Martínez, Daniel; Aguirre, María Belén; Logarzo, Guillermo; Hight, Stephen D.; Triapitsyn, Serguei; Diaz‐Sotero, Hilda; Diniz Vitorino, Marcelo; Hasson, Esteban
Abstract: Cryptic taxa have often been observed in the form of host‐associated species that diverged as the result of adaptation to alternate host plants. Untangling cryptic diversity in species complexes that encompass invasive species is a mandatory task for pest management. Moreover, investigating the evolutionary history of a species complex may help to understand the drivers of their diversification. The mealybug Hypogeococcus pungens was believed to be a polyphagous species from South America and has been reported as a pest devastating native cacti in Puerto Rico, also threatening cactus diversity in the Caribbean and North America. There is neither certainty about the identity of the pest nor the source population from South America. Recent studies pointed to substantial genetic differentiation among local populations, suggesting that H. pungens is a species complex. In this study, we used a combination of genome‐wide SNPs and mtDNA variation to investigate species diversity within H. pungens sensu lato to establish host plant ranges of each one of the putative members of the complex, to evaluate whether the pattern of host plant association drove diversification in the species complex, and to determine the source population of the Puerto Rican cactus pest. Our results suggested that H. pungens comprises at least five different species, each one strongly associated with specific host plants. We also established that the Puerto Rican cactus pest derives from southeastern Brazilian mealybugs. This is an important achievement because it will help to design reliable strategies for biological control using natural enemies of the pest from its native range. Abstract : Hypogeococcus pungens is a species complex native to South America. Some of its members are cactophilic, and one of them has been reported as a pest threatening cactus diversity in the Caribbean and North America. Using a combination of genome‐wide SNPs and mtDNA, we found that the complex comprises at least five different species, each strongly associated with specific host plants. Our study also shows that the Puerto Rican cactus pest derives from southeastern Brazilian mealybugs. These results will help to design reliable strategies for biological control using natural enemies of the pest from its native range.